2017
DOI: 10.3390/ijerph14111380
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Bone Fracture in Female Trauma Patients Based on Risks of Osteoporosis Assessed using the Osteoporosis Self-Assessment Tool for Asians Score

Abstract: Background: Osteoporotic fractures are defined as low-impact fractures resulting from low-level trauma. However, the exclusion of high-level trauma fractures may result in underestimation of the contribution of osteoporosis to fractures. In this study, we aimed to investigate the fracture patterns of female trauma patients with various risks of osteoporosis based on the Osteoporosis Self-Assessment Tool for Asians (OSTA) score. Methods: According to the data retrieved from the Trauma Registry System of a Level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Femoral shaft and distal fractures can occur in younger patients without any evidence of osteoporosis, usually as a result of a high-energy trauma such as a motor vehicle accident or motorcycle accident [8, 9, 30, 31]. The impact of the energy transmitted to the bone is generally greater in traffic accidents than in fall accidents, and the point of impact to the femur is not limited to the greater trochanter, which commonly occurs in falls.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral shaft and distal fractures can occur in younger patients without any evidence of osteoporosis, usually as a result of a high-energy trauma such as a motor vehicle accident or motorcycle accident [8, 9, 30, 31]. The impact of the energy transmitted to the bone is generally greater in traffic accidents than in fall accidents, and the point of impact to the femur is not limited to the greater trochanter, which commonly occurs in falls.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly individuals are at the greatest risk of a fall accidents [1,2] and their consequences, such as fractures, immobility, and sometimes even death [3][4][5][6][7]. In addition to pain, a femoral fracture results in a curtailment of physical activity, increased dependence, and rapid worsening of the health status.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a study reported that patients with a highrisk OSTA score were 8.3 times higher to experience fractures than patients with low OSTA scores. 37 The sensitivity of the OSTA score was 45.83%, which means that as much as 45.83% of patients who obtained positive diagnostic results have obtained fractures, and the specificity of the OSTA score was 50%, so 50% of all healthy patients will have a negative diagnostic test. The PPV of the OSTA score was 57.89%, which means that the probability of patients with a positive test result who truly have fractures was 57.89%, while the NPV was 38.09% which means that the probability of patients with a negative test result who have no fractures was as much as 38.09%.…”
Section: Original Articlementioning
confidence: 98%